First observations of seasonal bottom water deoxygenation off the Gironde estuary (Bay of Biscay, North East Atlantic) - Dubosq, Nicolas; Schmidt, Sabine; Sudre, Joël; Rigaud, Sylvain; Lamarque, Bastien; Danilo, Martin; Grémare, Antoine; Deflandre, Bruno (Frontiers in Marine Science, 2022)
Although not systematically considered as oxygen minimum zones, River-dominated Ocean Margins are sensitive to oxygen depletions. For example, the continental shelf off the Gironde, which flows into the Bay of Biscay, had not yet been studied from this perspective although recent simulations suggested that this area should already have experienced deoxygenations in recent decades. To fill this gap, profiles of temperature, salinity and dissolved oxygen were performed in the water column of the continental shelf off the Gironde during seven cruises distributed over the different seasons between 2016 and 2021. Turbidity, chlorophyll-a and pH were also measured during some of these cruises. In winter, the water column was slightly stratified due to high river flows. Then, a seasonal thermal stratification was present from spring to autumn. Similarly, dissolved oxygen showed a seasonal dynamic with: a well-oxygenated water column in winter, an oxygen oversaturation in the first 20 meters during the spring bloom, and then a progressive oxygen depletion in bottom waters until reaching an oxygen saturation minimum down to 45% in autumn. These deoxygenations are explained by the seasonal stratification that isolates the bottom waters from spring to autumn, and are likely enhanced by the advection of deoxygenated waters from the north of the Bay of Biscay and the settling of the organic matter produced in surface waters. A better understanding of these processes in the context of global warming undoubtedly requires better documentation of dissolved oxygen variability through the implementation of a long-term and continuous in situ monitoring.